Sexual Activity and Satisfaction in Cervical Cancer Patients - Has, Eka Mishbahatul M.; Kusumaningrum, Tiyas; Rahayu, Ria Restu Resmi; Hadisuyatmana, Setho (International Journal of Psychosocial Rehabilitation, 2020)
Sexuality is an important part of daily quality of life for cervical cancer patients, both before, during, and after post-cancer treatment. Diagnosis and treatment of cervical cancer has provided a change in the patient’s sexual function, resulting in changes in sexual activity and sexual satisfaction. This study aimed to determine the correlation between sexual activity and sexual satisfaction in cervical cancer patients at Kota Surabaya. This study used a correlational design. The total sample was 76 cervical cancer patients obtained using a purposive sampling technique. The independent variable in this study was sexual activity. The dependent variable in this study was sexual satisfaction measured using the Sexual Satisfaction Scale for Women (SSS-W 30-items). Statistical test analysis used Chi-square (α=0.05). Most of the respondents (90.8%) reported that they were sexually active and satisfied with their current sexual lives (76.32%). Statistical test results showed no different between sexual activity and sexual satisfaction in cervical cancer patients in Surabaya (p=0.346). There was no difference in sexual satisfaction levels between sexually active and inactive cervical cancer patients. The usual forms of sexual activity performed by cervical cancer patients involved holding hands, kissing and hugging. The most prominent parameters of sexual satisfaction were the parameters of communication, compatibility, and personal concern. The involvement of health workers in efforts to prevent and overcome the effects of sexual dysfunction for cervical cancer patients and their partners.